Association of renin angiotensin system gene polymorphism with chronic kidney disease in type 2 diabetic patients - GAO Yan-ting; LIANG Yan; SUN Yan; LI Zhen-jiang (Linchuang shenzangbing zazhi)
Objective To investigate the relationships of gene polymorphisms of angiotensinogen(AGT)and angiotensin Ⅱ type 1 receptor(AT1 R)with chronic kidney disease in type 2 diabetic patients.Methods The allele frequency and the genotype distribution of AGT M235 Tand AT1 R A1166 Cgene polymorphism were studied in 28 type 2 diabetic patients with diabetic nephropathy(DN),30 type 2 diabetic patients with non-diabetic renal disease(NDRD),18 type 2 diabetic patients with both DND and NDRD(DN+NDRD)and 30 healthy controls by polymerase chain reaction(PCR).Results Membranous nephropathy(MN)and IgA nephropathy were the main pathological profiles of the NDRD group,and MN,IgA nephropathy and benign arteriolar nephrosclerosis(BNS)were the main pathological profiles of the DN+NDRD group.No significant differences were found in pathological profiles between the two groups.The frequency of AGT-TT genotype was significantly higher in DN and DN+NDRD groups than in NDRD and healthy control groups(P<0.05).The frequency of AGT T allele was significantly higher in DN and DN+NDRD groups than in NDRD(P<0.05)and healthy control(P<0.01)groups.No significant differences were found in AGT-TT genotype or AGT T allele between DN and DN+NDRD groups,or between NDRD and healthy control groups.No significant differences were found in AT1 R A1166 C polymorphism among all groups.AGT M235 T-TT genotype was the risk of low estimated glomerular filtration rate(eGFR).Conclusions AGT-TT genotype and AGT T allele may be association with the increased risk of DN and DN+NDRD in type 2 diabetic patients.There may be no association between AGT-TT genotype or AGT T allele and the initiation of NDRD in type 2 diabetic patients.There may be no association between AT1 RA1166 Cpolymorphism with chronic kidney disease in type 2 diabetic patients.